Integrasi Spiritual dan Pedagogi Modern: Studi Komparatif Pemikiran Abdullah Nashih Ulwan dan Maria Montessori Terhadap Pembentukan Karakter Siswa di Era Digital - Wafi, Abdul; Musleh; Ramadhan, Fahim Abu; Mujahidin, Ahmad; Khoiriyah (Educational Research Center, 2026)
The development of the digital era has significant implications for the educational process, particularly in the formation of student character. On the one hand, technology offers easy access to information and pedagogical innovation; on the other hand, it raises serious challenges in the form of moral value degradation, spiritual crisis, and character disorientation. This article aims to analyze and compare the thoughts of Abdullah Nashih Ulwan and Maria Montessori regarding the integration of spiritual dimensions and modern pedagogy in the formation of student character, and their relevance in the digital era. This study uses a qualitative approach based on library research with content analysis methods on the main works of both figures and relevant supporting literature. The results show that Abdullah Nashih Ulwan emphasizes a spiritual-transcendental foundation based on faith, morals, and exemplary values ​​as the core of character education, while Maria Montessori prioritizes a humanistic pedagogical approach that is child-centered, directed freedom, and a conducive learning environment. Although originating from different epistemological and cultural backgrounds, both thoughts have a common point in the orientation of the formation of the whole person (holistic human development). This study contributes theoretically by offering an integrative framework between spirituality and modern pedagogy, and practically provides a conceptual basis for the development of a character education model that is adaptive to the challenges of the digital era without losing its ethical and spiritual dimensions.